Restrictive Blood Transfusion Protocol in Malignant Upper Gastrointestinal and Pancreatic Resections Patients Reduces Blood Transfusions with No Increase in Patient Morbidity - Wehry, John (Am J Surg, 2015)
BACKGROUND: The purpose of this study was to determine the impact of a restrictive blood transfusion protocol on the number of transfusions performed and the related effect on patient morbidity. METHODS: A cohort study was performed using our prospective database with information from 01/01/2000–06/01/2013. The restrictive blood transfusion protocol was implemented in 9/2011, so this date served as the separation point for the date of operation criteria. RESULTS: For the study, 415 patients undergoing operation for an abdominal malignancy were reviewed. Following the restrictive blood transfusion protocol the percentage of patients that received blood dropped from 35.6% to 28.3%. The percentage of patients that experienced perioperative complication was significantly higher in transfused patients compared to those that did not receive blood(p=0.0001). There was no statistical significance observed between the four groups for the length of stay at the hospital following their procedure. CONCLUSION: The restrictive blood transfusion protocol resulted in a reduction of the percentage of patients transfused, and there was no evidence to suggest that it negatively impacted the outcomes of patients in this group.